The study skills; an educational implication on students’ performance in secondary school mathematics - Odiri Onoshakpokaiye (MEJ (Mathematics Education Journal), 2021)
There is poor performance in mathematics among secondary school students in Delta State, Nigeria. Teachers, Parents, the government are all complaining about the poor performance of students in mathematics, and they are trying to find out how this problem can be solved. Many kinds of research have been carried out trying to find out the real cause of students’ poor performance in secondary mathematics, but they fail to focus much attention on the variable ‘study skills’ as one of the causes. The study is a survey type. Five hundred (500) students were sampled from 25 Government secondary schools, Delta State of Nigeria, through random sampling. The instrument used in gathering data for this study were the students’ Study Skills Questionnaire (SSSQ) and centrally set examination results from the state ministry of education. The result from the state ministry of education was used to gather data on the students’ performance in mathematics, while the questionnaire was used to gather information on students’ study skills. Two hypotheses were stated to guide the study, which was tested at a 0.05 level of significance using the SPSS and t-test statistic to analyze the data obtained. The result shows that there is a significant influence on students’ study skills and their performance in Mathematics. There was a significant difference between students who possess good study skills and those with bad study skills.